Investigating the stability of second phase particles in Zr-Nb alloys under irradiation - He, G; Liu, J; Li, K; Hu, J; Mir, AH; Lozano-Perez, S; Grovenor, C (Elsevier, 2019)
The stability of the β-Nb Second Phase Particles (SPPs) in two types of Zr–Nb alloys (recrystallised Zr-1.0Nb and Zr-2.5Nb) was studied by in-situ heavy ion irradiation in a transmission electron microscope (TEM), combined with ex-situ analysis by energy dispersive x-ray spectroscopy (EDX). TEM thin foils were irradiated by 1 MeV Kr+ ions at four different temperatures from 50 K to 873 K, and by 350 keV Kr+ ions at different doses up to 39dpa. The change in size of individual β-Nb SPPs has been measured quantitatively, and the degradation mechanisms under irradiation at different temperatures discussed. It has been shown that the Nb redistribution between the SPPs and the Zr matrix is governed both by radiation induced mixing and local diffusion in the surrounding Zr matrix. Under the radiation conditions reported in this study, the β-Nb SPPs have shown remarkably stability against irradiation, and the extent of Nb redistribution between the SPPs and Zr matrix is very limited under all experimental conditions.